Refining the scalar and tensor contributions in τ → πππν τ decays - Juan José Sanz-Cillero; Olga Shekhovtsova (Journal of High Energy Physics, 2017)
Abstract In this article we analyze the contribution from intermediate spin-0 and spin-2 resonances to the τ → νπππ decay by means of a chiral invariant Lagrangian incorporating these mesons. In particular, we study the corresponding axial-vector form-factors. The advantage of this procedure with respect to previous analyses is that it incorporates chiral (and isospin) invariance and, hence, the partial conservation of the axial-vector current. This ensures the recovery of the right low-energy limit, described by chiral perturbation theory, and the transversality of the current in the chiral limit at all energies. Furthermore, the meson form-factors are further improved by requiring appropriate QCD high-energy conditions. We end up with a brief discussion on its implementation in the Tauola Monte Carlo and the prospects for future analyses of Belle’s data.